The right to live in health : medical politics in postindependence Havana - Rodríguez, Daniel A., 1976- (Chapel Hill : The University of North Carolina Press, 2020)
"Rodríguez describes how medicine and new public health projects infused republican Cuba's statecraft, powerfully shaping the lives of Havana's residents. He underscores how various stakeholders, including women and people of color, demanded robust government investment in quality medical care for all Cubans, a central national value that continues today. On a broader level, Rodríguez proposes that Latin America, at least as much as the United States and Europe, was an engine for the articulation of citizens' rights, including the right to health care, in the twentieth century"--
Five: With All, and for the Good of All: Race, Poverty, and Tuberculosis -- Six: To Fight These Powerful Trusts and Free the Medical Profession: Spanish Mutualism, Medicine, and Revolution, 1925-1935 -- Conclusion: The Right to Live in Health in Postcolonial Havana -- Notes -- Bibliography -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- Y
Includes bibliographical references and index.
JSTOR
Keywords: Cuba. -- Secretaría de Sanidad y Beneficencia -- History; Cuba. -- Secretaría de Sanidad y Beneficencia -- History; Cuba. -- Secretaría de Sanidad y Beneficencia; Public health -- Cuba -- History -- 20th century; Medical policy -- Cuba -- 20th century; Right to health -- Cuba -- History -- 20th century; Public Health -- history; Health Policy -- history; Health Services -- history; Right to Health -- history; Cuba; Santé publique -- Cuba -- Histoire -- 20e siècle.; Politique sanitaire -- Cuba -- 20e siècle.; Droit à la santé -- Cuba -- Histoire -- 20e siècle.; SOCIAL SCIENCE / Ethnic Studies / General; Medical policy; Public health; Right to health; Cuba; 1900-1999; History